A GOOD RESULT IN COMBINATION OF LARGE SUPERIOR RECTUS RECESSION AND PRISMATIC GLASSES IN UNILATERAL DISSOCIATION VERTICAL DEVIATION: A CASE REPORT: Poster Presentation - Case Report - Resident - Nur Fitriana Corprianti Marchilia; Prastyani, Reni (Majalah Oftalmologi Indonesia, 2023)
Introduction : Severe DVD is one of the indications for surgery. There are guidelines recommended for management based on grading of severity and the surgeon’s preference. Large recession of superior rectus muscle and prismatic glasses yield good result in unilateral DVD reported in this paper. Case Illustration : A 21 year-old student stated difficulty in working with his microscope since 2 years ago. He had a history of double vision since childhood. The visual acuity in both eyes were 5/5. Qualitative strabismus examination resulted in hypertropia RE and intermittent exotropia. When the occluder was removed from RE, a non fixating eye would appear elevated and did not correspond with the contralateral eye hypotropia. Krimsky test revealed RE hypertropia 30? PD, exotropia 10? PD. Sensory evaluation using WFDT was normal in near and crossed diplopia in distance. Patient diagnosed with unilateral DVD then underwent superior rectus recession in 10 mm. The following month, patient was still experiencing vertical diplopia. The patient was given 3 PD prismatic glasses. Consequently, diplopia was absent and stereoacuity test using TNO was 480 seconds of arch Discussion : DVD can’t be fully corrected by surgery due to central cortical innervational problem. The residual symptom can be corrected by conservative management. Large SR recession in combination with prismatic glasses was found to improve vertical deviation and reduce diplopia. Conclusion : While large superior rectus recession can significantly improve vertical deviation, it can not completely remove binocular symptom